Empowering Communities through Vegetable Innovation: A Case Study of Green Mustard Nuggets in Petiyintunggal Village - Siti Shoimah; Ari Rusnia Widhya F Widhya; Cinta Ayu Amaliyah Amaliyah; Hasmah Hasmah; Handariyatul Maimunah (Shof Journal of Social Impact, 2024)
Vegetable consumption is crucial for a balanced diet, providing essential vitamins, minerals, and fiber. In Indonesia, however, average vegetable intake is significantly below the World Health Organization's recommendation, contributing to health issues like stunting, particularly among vulnerable groups such as children and pregnant women. To address this, a community service initiative by Universitas Islam Darul 'Ulum Lamongan focused on Petiyintunggal Village, East Java, aimed to enhance vegetable consumption through green mustard nugget production. The program targeted PKK (Family Welfare Empowerment) members, providing them with training in nugget preparation, from ingredient handling to packaging. Results showed significant improvements in participants' knowledge and skills, with post-training assessments indicating a rise in understanding of nutritional benefits, production processes, and packaging. This initiative successfully combined health benefits with economic opportunities, contributing to local economic resilience and sustainable community development.